Falls efficacy instruments for community-dwelling older adults: a COSMIN-based systematic review - Shawn Leng-Hsien Soh (BMC Geriatrics, 2021)
Abstract Background Falls efficacy is a widely-studied latent construct in community-dwelling older adults. Various self-reported instruments have been used to measure falls efficacy. In order to be informed of the choice of the best measurement instrument for a specific purpose, empirical evidence of the development and measurement properties of falls efficacy related instruments is needed. Methods The Consensus-based Standards for the Selection of Health Measurement Intruments (COSMIN) checklist was used to summarise evidence on the development, content validity, and structural validity of instruments measuring falls efficacy in community-dwelling older adults. Databases including MEDLINE, Web of Science, PsychINFO, SCOPUS, CINAHL were searched (May 2019). Records on the development of instruments and studies assessing content validity or structural validity of falls efficacy related scales were included. COSMIN methodology was used to guide the review of eligible studies and in the assessment of their methodological quality. Evidence of content validity: relevance, comprehensiveness and comprehensibility and unidimensionality for structural validity were synthesised. A modified GRADE approach was applied to evidence synthesis. Results Thirty-five studies, of which 18 instruments had been identified, were included in the review. High-quality evidence showed that the Modified Falls Efficacy Scale (FES)-13 items (MFES-13) has sufficient relevance, yet insufficient comprehensiveness for measuring falls efficacy. Moderate quality evidence supported that the FES-10 has sufficient relevance, and MFES-14 has sufficient comprehensibility. Activities-specific Balance Confidence (ABC) Scale–Simplified (ABC-15) has sufficient relevance in measuring balance confidence supported by moderate-quality evidence. Low to very low-quality evidence underpinned the content validity of other instruments. High-quality evidence supported sufficient unidimensionality for eight instruments (FES-10, MFES-14, ABC-6, ABC-15, ABC-16, Iconographical FES (Icon-FES), FES–International (FES-I) and Perceived Ability to Prevent and Manage Fall Risks (PAPMFR)). Conclusion Content validity of instruments to measure falls efficacy is understudied. Structural validity is sufficient for a number of widely-used instruments. Measuring balance confidence is a subset of falls efficacy. Further work is needed to investigate a broader construct for falls efficacy.